Finite element analysis for mechanical response of Ti foams with regular structure obtained by selective laser melting. (15th September 2015) - Cho, Hoon-Hwe; Cho, Yigil; Han, Heung Nam
Graphical abstract: Abstract: Metal-based cellular materials with periodic structures are currently the preferred choice as bone/cartilage implants under load-bearing conditions due to their controlled pore interconnectivity and porosities. This report presents a new methodology for the structural analysis of periodic cellular materials using X-ray microtomography and dual-level finite element modeling (FEM). A three-dimensional (3D) structure of periodic titanium foam produced using selective laser melting (SLM) is obtained using an X-ray microtomography. A dual-level FEM based on the 3D structure is used to simulate the deformation behavior of titanium foam with a regular structure under uniaxial compression, and the computed results are compared directly with the interrupted uniaxial compression experiments performed on the deformed 3D structures. The deformation behaviors of simplified structures with cylindrical and hexahedral struts are simulated, and the computed results demonstrate that unavoidable defects in the actual structure affect the mechanical stability significantly. Additionally, buckling-induced deformation behavior is analyzed by introducing an imperfection in the actual and simplified structures. The effects of certain selected process variables, such as internal angle and diameter, are also examined through a series of process simulations.